Rejected sago starch as a coating material to mitigate urea-nitrogen emission - Kavitha, Rajan; Latifah, Omar; Ahmed, Osumanu Haruna; Primus, Walter Charles; Susilawati, Kasim (MDPI, 2022)
Urea–nitrogen is commonly lost through ammonia (NH3) volatilization, denitrification, and nitrate (NO3−) leaching. Rejected sago starch (RSS), which is a by-product of sago flour extraction, could be used to minimize NH3 volatilization from urea. Urea granules were coated with different concentrations of RSS (2%, 3%, 4%, 5%, and 6%), and their effects on NH3 emission, soil pH, exchangeable ammonium (NH4+), and available NO3− were determined. The urea was coated with RSS and homogenized using a mini rotary machine. The RSS-coated urea granules were dyed to differentiate their concentrations. The effectiveness of the RSS as a coating material was determined using a closed-dynamic air flow system. The soil used in the NH3 volatilization was the Bekenu series (Sandy loam, Typic Paleudults). This study compared seven different mixture treatments: soil alone (S), 5 g of uncoated urea (U), 5 g of 2% RSS-coated urea (CU1), 5 g of 3% RSS-coated urea (CU2), 5 g of 4% RSS-coated urea (CU3), 5 g of 5% RSS-coated urea (CU4), and 5 g of 6% RSS-coated urea (CU5). Urea coated with RSS, particularly CU1, effectively minimized NH3 loss and improved the retention of soil exchangeable NH4+ and available NO3− compared with uncoated urea because the RSS serves as a barrier to minimizing the concentration of NH3 from urea hydrolysis. Urea could be coated with RSS at the 2% concentration to enhance urea–N efficiency through a reduction in NH3 emission from urea. RSS-coated urea could be an alternative for farmers because of its controlled release of N and economical benefits. Field planting using rice as a test crop to solidify the effectiveness of RSS-coated urea in improving N retention from urea is still ongoing.